Converter interaction stability analysis tools - Andersson, Rasmus; Rasmusson, Victor (My University, 2026)
As a result of efforts to reduce greenhouse gas emissions, the use of renewable energy has increased and, with these, power sources being integrated into the power system through power electronic interface devices (PEIDs). The dynamic behavior that PEIDs introduce has resulted in new stability challenges. Multiple cases of undamped oscillations originating from converters interacting with other grid elements has already occurred and understanding the instability mechanism is essential. This thesis investigates methods and tools for converter interaction stability analysis and develops an automated tool for frequency domain stability assessment. Existing open source tools and different methodologies are evaluated with respect to their accuracy, computational efficiency and applicability. Requirements in the area from transmission system operators (TSO) are also reviewed. The tool proposed in this thesis is based on sequence-domain frequency injections with multi-frequency perturbations to improve computational efficiency. Both Single-Input-Single-Output (SISO) and Multiple-input-Multiple-Output (MIMO)-based analysis methods are implemented and compared, including Nyquist-based criterion, disk margin evaluation and passivity-based a valuation. The tool is validated against an existing mathematical framework and benchmarked against already existing tools, as well as tested on a detailed MMC model. The results show that the developed framework provides accurate, fast and detailed results when compared to established tools. The studies performed also show the importance of the perturbation magnitude when it comes to analyzing non ideal systems where insufficient or excessive injection magnitude can lead to noisy measurements or non-linear effects. The comparison between SISO and MIMO methods has provided similar results for a given system. The system under study has been varied to increase cross coupling on the converter admittance, and it has been found that SISO methods can provide inaccurate conclusions regarding system stability. The outcome from the review of the transmission system operator (TSO) requirements related to converter interaction stability is that, in general, there is no suggested method available, except for the Swedish TSO. Typically, the methodology and acceptance criteria regarding converter interaction stability is agreed with TSOs at the start of each project. With regards to stability margins, a more robust approach can be the use of a disk margin, due to its multi-loop capability in a MIMO system and the ability to analyze phase and gain at the same time.
Keywords: Small signal stability, Converter interaction analysis, Frequency analysis, Python, PSCAD, Impedance based stability analysis, Passivity-based approach, Converter admittance grid impedance, Positive sequence,Negative sequence